PERENCANAAN PRODUKSI AGREGAT PADA KONVEKSI KREASIMUDA DIVISION DI PAGEDANGAN, TANGERANG - Vatmala, Eliatika; Setiawan, Putu Yudi (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.01.TAHUN.2024, 2024)
Aggregate production planning is useful for knowing what products will be produced, how many products will be produced, minimizing production costs, and on time delivery. The purpose of this study is to identify and explain the trend of demand and the most efficient aggregate production planning in the Kreasimuda Convection Division. This research was conducted in the city of Tangerang, precisely in the Kreasimuda Convection Division. This research is included in descriptive research with a quantitative approach. The method used to calculate production demand forecasting is the 3-period moving average method and the exponential smoothing method = 0.2, then the method that produces the smallest MAPE value is chosen. The strategy used to calculate aggregate production planning is the level strategy and chase strategy, then the best strategy is chosen that produces the lowest production cost. The result of the research that has been done is that the best production demand forecasting method is the exponential smoothing method with MAD 230, MSE 129,762, and MAPE 14% with the demand trend formed is a stationary demand trend (horizontal). In aggregate production planning, the strategy that produces the lowest production costs is the level strategy of Rp. 156,241,869 per year.